ANTHROPOMETRIC MEASUREMENTS AND NUTRITIONAL DEFICIENCIES AMONG ADOLESCENT GIRLS IN EAST KHASI HILLS, MEGHALAYA. - SARA K JYRWA (The Journal of Research ANGRAU, 2025)
The present study was conducted among 467 unmarried adolescent girls (13-18 yrs) with an aim to assess the anthropometric measurements and to screen for nutritional deficiencies among adolescent girls in East Khasi Hills District of Meghalaya, India. Data on Sociodemographic and clinical examination were collected using a pre-tested semi-structured questionnaire. Parameters viz., height and weight were recorded and BMI was calculated. From the 476 adolescent girls, 55.88 % were aged between 13-15 years, 63.03 % belonged to nuclear families, 69.96 % followed Christianity and 33.82 % belonged to low-income groups. The average standing height and body weight were significantly lower than the ICMR standards (p < 0.01) demonstrating growth deficit. The BMI analysis showed that 20 % of the adolescent girls were underweight, 6.09 % were overweight and 1.26 % were obese. Iron Deficiency Anaemia (IDA) was noticed in 35.5 % of adolescent girls, indicating a moderate public health concern. Vitamin C deficiency was observed in 19.6 % of the adolescent girls showing signs of spongy and bleeding gums, also classified as a mild public health problem. Vitamin A deficiency (VAD) was observed in 5 % of adolescent girls and it was classified as a mild public health problem. Additionally, 33.3 % of adolescent girls had Vitamin D deficiency, presenting with muscle and bone pain. In view of these findings, implementing targeted micronutrient interventions is imperative to mitigate deficiencies and strengthen the overall nutritional profile.